2009
DOI: 10.1158/0008-5472.can-09-0075
|View full text |Cite
|
Sign up to set email alerts
|

ERG Is a Megakaryocytic Oncogene

Abstract: Ets-related gene (ERG) is a member of the ETS transcription factor gene family located on Hsa21. ERG is known to have a crucial role in establishing definitive hematopoiesis and is required for normal megakaryopoiesis. Truncated forms of ERG are associated with multiple cancers such as Ewing's sarcoma, prostate cancer, and leukemia as part of oncogenic fusion translocations. Increased expression of ERG is highly indicative of poor prognosis in acute myeloid leukemia and ERG is expressed in acute megakaryoblast… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
124
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(128 citation statements)
references
References 37 publications
3
124
0
1
Order By: Relevance
“…Escalating healthcare expenditures triggers cost crisis in developing nations. This poses various challenges in resource allocation and budgeting (4,5). On the demand side, patient expectations, demographic characteristics, and disease models have changed.…”
Section: Introductionmentioning
confidence: 99%
“…Escalating healthcare expenditures triggers cost crisis in developing nations. This poses various challenges in resource allocation and budgeting (4,5). On the demand side, patient expectations, demographic characteristics, and disease models have changed.…”
Section: Introductionmentioning
confidence: 99%
“…High ERG expressers were associated with an inferior clinical outcome (Marcucci et al, 2005;Baldus et al, 2006). The pathogenesis of ERG was also observed in sublethally irradiated mice transplanted with ERG transduced progenitor cells, whereby megakaryoblastic leukemia developed (Salek-Ardakani et al, 2009). Thus, several clinical and experimental studies indicate that ERG contributes to the pathogenesis in cancer and leukemia; however, the underlying biological mechanisms are not yet fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…GATA1 knockdown mice accumulate immature erythroid progenitors [45], and when transgenically 'rescued' with GATA1s these mice have an abnormal accumulation of CD41+ megakaryocytic progenitors [46]. Furthermore, forced expression of GATA1s in fetal hematopoietic progenitors from mice bearing wild-type GATA1 causes marked expansion of megakaryoblastic progenitors [25]. Toki et al [47] also revealed that GATA1s promotes megakaryocyte proliferation more profoundly than that induced by GATA1 deficiency, supporting a gain-offunction mechanism for GATA1s.…”
Section: Gata1 Mutation Induces Tam In Ds Neonatesmentioning
confidence: 99%
“…Ts65Dn mice, which are trisomic for 104 orthologs of Hsa21 genes, display persistent macrocytosis and develop a myeloproliferative disease characterized by megakaryocyte hyperplasia and dysplasia, and myelofibrosis [19]. Several genes on Hsa21, such as RUNX1, ETS2, ERG, GAPBA, BACH1, and DYRK1A, encode proteins relating to hematopoiesis and leukemogenesis [9,[21][22][23][24][25][26]. Further analysis of the models may reveal the effect of chromosome 21 gene dosage on human hematopoiesis and hematological malignancies.…”
Section: Abnormal Hematopoiesis In Dsmentioning
confidence: 99%